Politics in uniform : military officers and dictatorship in Brazil, 1960-80 - Chirio, Maud (Pitt Latin American series., 2018)
"Between 1964 and 1985, Brazil lived under the control of a repressive, anticommunist regime, where generals maintained all power. Respect for discipline and the absence or any and all political activity was demanded of lower-ranking officers, while their commanders ran the highest functions of state. Despite the circumstances, dozens of young captains, majors, and colonels believed that they too deserved to participate in teh exercise of power. For two decades they carried on a clandestine political life that strongly influenced the regime's evolution."--Provided by publisher.